2012
DOI: 10.1007/s12011-012-9483-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trypsin and Mucin on Heme Iron Bioavailability in Humans

Abstract: Trypsin is the only human gastrointestinal protein that evaluated the affects of heme iron absorption. However, this effect depends on how heme iron is ingested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It can be seen that the iron solubility of ferrous sulphate after pancreatic digestion was still the lowest among five different iron sources, followed by haemin chloride 19.47%, haemin chloride plus collagen complex 23.11%, haemoglobin 32.88% and the iron solubility of haem‐peptides was the highest of 45.98%. This result was in accordance with the results of previous reports (Vaghefi et al ., 2002; Cediel et al ., 2012). Vaghef et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be seen that the iron solubility of ferrous sulphate after pancreatic digestion was still the lowest among five different iron sources, followed by haemin chloride 19.47%, haemin chloride plus collagen complex 23.11%, haemoglobin 32.88% and the iron solubility of haem‐peptides was the highest of 45.98%. This result was in accordance with the results of previous reports (Vaghefi et al ., 2002; Cediel et al ., 2012). Vaghef et al .…”
Section: Resultsmentioning
confidence: 99%
“…As for the better absorption of haemoglobin than haemin chloride, Cediel et al . (2012) reported that trypsin digestion could increase the absorption of haem iron as haemoglobin, but decreases the absorption of haem iron as haemin chloride, because the trypsin could promote the haemin chloride polymerisation at the alkaline environment and consequently decreased the haem iron intestinal absorption. But Pizarro et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that animal derived proteins enhance the absorption of non heme Fe [ 12 , 13 , 14 , 15 ], while legume proteins from soybeans [ 16 , 17 , 18 ], and other plant proteins decrease non heme Fe absorption [ 19 , 20 , 21 ]. Studies have shown increases in heme Fe absorption in the presence of animal proteins and hemoglobin [ 22 , 23 , 24 , 25 ], relative to the types of amino acids present [ 26 ], and the combination of hemoglobin with trypsin [ 27 ]. However, studies showing how plant proteins affect heme Fe absorption are scarce.…”
Section: Introductionmentioning
confidence: 99%